Molecular Docking and Pharmacokinetic Studies of Some New pyridyl and hydrazinyl bearing thiazole Derivatives as Potential DNA gyrase Inhibitors (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
An essential bacterial protein called DNA gyrase is involved in transcription and replication and stimulates the negative super-coiling of the circular DNA found in bacteria. Since its inhibition causes bacterial mortality, DNA gyrase is a well-known target for antibacterial drugs. Gyrase is inhibited by quinolones, coumarins, and cyclothialidines. The objective of the present study is to evaluate the binding interaction of pyridyl and hydrazinyl-bearing thiazole compounds with DNA gyrase inhibitors and also check the ADME properties of all compounds. We performed docking and pharmacokinetic studies of 28 novel hypothetical compounds. Interacting amino acids of receptor DNA gyrase with reference drug prothionamide were VAL 167, VAL 71, ILE 78, and THR 165 and binding affinity was found to be -5.61 kcal/mol. Most of our docked compounds also show interaction with amino acids VAL 71 and ILE 78 with superior binding affinity. Molecular docking suggests that all the synthesized derivatives have shown higher level binding affinity in contrast to standard drug prothionamide and have an acceptable range of ADME properties.